REMOTE SENSING, GIS AND PUBLIC HEALTH - HIROKl SUGIMORI (International Journal of Remote Sensing and Earth Sciences, 2004)
The role of remote sensing (RS) and Geographic Information Systems (GIS) in publichealth is potentially great. As computer technology it continues to transform our ability to gather, analyze, and map health data, new roles for RS and GIS in public health may emerge.